2016
DOI: 10.1016/j.bbrep.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Induction of IL-10-producing regulatory B cells following Toxoplasma gondii infection is important to the cyst formation

Abstract: Toxoplasma gondii is a protozoan parasite that infects humans and animals via congenital or postnatal routes. During parasite infection, IL-10-producing Bregs are stimulated as part of the parasite-induced host immune responses that favor infection. In this study, we investigated whether T. gondii infection induces immune regulatory cells including IL-10-producing CD1dhighCD5+ regulatory B cells (Bregs) and whether Breg induction is critical for the development of chronic infection of T. gondii. Furthermore, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
(35 reference statements)
0
19
0
Order By: Relevance
“…The only difference between the two routes of administration was the IL-10 secretion by splenocytes of ID immunized sheep (not seen in IN sheep), suggesting that IL-10 could participate in favoring infection. Indeed, several studies have demonstrated that IL-10 production secreted during toxoplasmosis decreased host resistance and increased parasite burden (49). Concerning cells distribution following vaccination, increase of MHCII + cells in spleen and lymph nodes, especially for sheep vaccinated by intranasal route, may reflect induction of a cellular response suggesting that vaccination is effective.…”
Section: Discussionmentioning
confidence: 99%
“…The only difference between the two routes of administration was the IL-10 secretion by splenocytes of ID immunized sheep (not seen in IN sheep), suggesting that IL-10 could participate in favoring infection. Indeed, several studies have demonstrated that IL-10 production secreted during toxoplasmosis decreased host resistance and increased parasite burden (49). Concerning cells distribution following vaccination, increase of MHCII + cells in spleen and lymph nodes, especially for sheep vaccinated by intranasal route, may reflect induction of a cellular response suggesting that vaccination is effective.…”
Section: Discussionmentioning
confidence: 99%
“…Relative to protozoan parasites, still are rare the studies that investigate the role of Breg during the course of infection, but there is evidences that this B cell subtype is critically important in immune homeostasis [78−84]. In this context, Jeong and collaborators demonstrated that IL-10-producing CD1d hi CD5 + Breg cells are induced by products that are secreted by fully replicated tachyzoites and are essential to the chronicity of infection in Toxoplasma gondii murine model [83]. Considering that malaria and leishmaniasis, secular diseases caused by protozoans, remain two important causes of morbidity and/or mortality worldwide, insights into the role of Breg cells could provide the development of new therapeutic and vaccine strategies.…”
Section: Insights About the Role Of Breg Cells In The Course Of Infecmentioning
confidence: 99%
“…Nonetheless, a proinflammatory cytokine storm that would presumably follow T. gondii infection does not occur, because it is downregulated by high IL-10 release (46). Therefore, IL-10 is critical for establishing a chronic toxoplasmosis phase, associated with formation of T. gondii type II strains (47). Consistently, even when infected with avirulent Type II parasites, IL-10-deficient mice overproduce IFN-g, TNF-a, and IL-12, leading to exacerbated inflammation, tissue injury, and premature death (29).…”
Section: Discussionmentioning
confidence: 99%
“…Induction of inflammatory mediators thus allows parasites access to different host tissues during early stages of infection. Subsequently, the production of anti-inflammatory mediators can fine-tune hostparasite coexistence during establishment of chronic toxoplasmosis (29,46,47). The second aspect to be considered concerns the potential application of recombinant forms of these MICs in immunotherapy against T. gondii infection.…”
Section: Discussionmentioning
confidence: 99%